2013
DOI: 10.7771/1541-5015.1323
|View full text |Cite
|
Sign up to set email alerts
|

Definitions and Uses: Case Study of Teachers Implementing Project-based Learning

Abstract: The purpose of this descriptive study was to explore inservice teachers' definitions of project-based learning (PjBL) and their accounts on the meaning of their PjBL implementations. A purposive sample of six teachers from grades four through twelve in public and private schools participated. Three themes evolved from inductive analysis: (1) teachers define PjBL through its perceived advantages on learning, (2) teachers vary in their use of PjBL over the continuum of the learning process, and (3) teachers adop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
127
0
16

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(172 citation statements)
references
References 20 publications
(23 reference statements)
7
127
0
16
Order By: Relevance
“…Though the end result is important, many researchers (Blumenfeld et al, 1991;Grant, 2011;Krajcik et al, 1994;Tamim & Grant, 2013) discuss the importance of assessing a variety of learning products in order to properly assess the critical thinking that takes place over the course of PjBL experiences. English and Kitsantas (2013) suggested that the use of formative reflective prompts can positively impact self-regulated learning through "encouraging autonomy and providing an explicit place for reflection at multiple points in a project" (p. 142), which are often documented as written journal entries.…”
Section: The Importance Of Assessing Reflection During Pjbl Experiencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the end result is important, many researchers (Blumenfeld et al, 1991;Grant, 2011;Krajcik et al, 1994;Tamim & Grant, 2013) discuss the importance of assessing a variety of learning products in order to properly assess the critical thinking that takes place over the course of PjBL experiences. English and Kitsantas (2013) suggested that the use of formative reflective prompts can positively impact self-regulated learning through "encouraging autonomy and providing an explicit place for reflection at multiple points in a project" (p. 142), which are often documented as written journal entries.…”
Section: The Importance Of Assessing Reflection During Pjbl Experiencesmentioning
confidence: 99%
“…Citing empirical research that explores goal orientations in PjBL learning contexts, Blumenfeld et al (1991) highlighted that when students adopt the notion that "learning is perceived and valued as an end in of itself " (p. 370), they are more likely to be motivated to learn and will engage in higher levels of cognitive and metacognitive stimulation. Despite the growing use of PjBL in K-12 educational environments, many researchers (Belland, French, & Ertmer, 2009;Catapano & Gray, 2015;English & Kitsantas, 2013;Krajcik et al, 1994;Tamim & Grant, 2013) acknowledge the pedagogical difficulties educators could potentially encounter as they implement PjBL, such as measuring learning outcomes over the course of the PjBL learning experience.…”
mentioning
confidence: 99%
“…The PBL literature includes studies investigating characteristics of effective cases (Edmondson, 1994;Harling & Misser, 1998;Hmelo-Silveres & Barrows, 2006;Jonassen, 2000;Jonassen & Hung, 2008), characteristics of cases in specific learning environments (Dabbagh & Dass, 2013), implementation of cases, (Albanese & Mitchell, 1993;Azer, Mclean, Onishi, Tagawa, & Scherpbier, 2013;Schmidt, Rotgans, & Yew, 2011), and perceptions of cases by students and facilitators (Sockalingam & Schmidt, 2011;Tamim & Grant, 2013). There is a scarcity of research investigating the process of case construction and how case-writers anticipate and plan for successful knowledge construction by students.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown the use of PBL improves students' learning and improves students' beliefs in their abilities to complete complex tasks in engineering (Householder & Hailey, 2012). PBL has been shown to improve students' attitudes toward learning, team communication, collaboration skills, and creativity as well as students' academic achievement in mathematics (Han, Capraro, R. & Capraro, 2015;Householder & Hailey, 2012;Tamim & Grant, 2013). PBL has also been shown to develop problem-solving and system thinking skills (Householder & Hailey, 2012).…”
Section: Improving High School Math Teachers' Confidence and Skills Imentioning
confidence: 99%
“…Engineering PBL can bring the four content areas together in a way that is meaningful to students. Tamim and Grant (2013) found teachers may have a difficult time implementing new instructional strategies like PBL. Many teachers lack the training necessary to confidently implement PBL in their classrooms and to assess student learning as a result of PBL.…”
Section: Improving High School Math Teachers' Confidence and Skills Imentioning
confidence: 99%